Pike River Coal - Quality Environmental Management (The Australasian Institute of Mining and Metallurgy, 2005)
A major new mine to be developed at Pike River during 2005 has been designed to have a minimal impact upon the environment, and an overall net conservation gain. The Pike River Coalfield is located on the West Coast of the South Island of New Zealand on the top of the Paparoa Range approximately 46 km north east of the coastal town of Greymouth. Pike River Coal Company Ltd (PRCC) holds a 40 year mining permit over the coalfield.   In October 2004, the Minister of Conservation granted PRCC access through 1.25 km of Department of Conservation land via an access agreement, and the Environment Court issued a number of consents for the development and operation of the mine, in addition to some existing consents.   The underground mine at Pike River is located under land administered by Department of Conservation, and has been designed to avoid or mitigate adverse environmental effects and integrate into the natural bush surroundings. The mine process has been designed to operate within an environmentally sensitive area and will incorporate technologically advanced methods of mining and processing. The mine process involves hydro mining of the coal, and transportation via a 12 km coal water slurry pipeline, to a dewatering complex located on PRCC land. This will ensure that traffic in the Pike River Catchment up to the mine is minimised.   An extensive series of management plans and monitoring programmes will be used to ensure that the environmental effects of the mine activities are minimised, by evaluating the performance of managerial procedures, and physical mechanisms in place to avoid or mitigate the effects. Trial mining and substance management plans in conjunction with an orthophoto and surface monitoring protocol will ensure that surface features, and water ways are protected from any adverse effects. The Blue Duck enhancement, and pest and predator control programme will help ensure that an overall net conservation gain is achieved.   Developing transparent working relationships and good communication with Department of Conservation, Iwi (Ngati Waewae and Ngai Tahu), and local environment groups has been and remains very important in the development of this project.